2022
DOI: 10.1212/wnl.0000000000200782
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Sex, Menopause, and White Matter Hyperintensities

Abstract: Background and ObjectivesMounting evidence implies that there are sex differences in white matter hyperintensity (WMH) burden in older people. Questions remain regarding possible differences in WMH burden between men and women of younger age, sex-specific age trajectories and effects of (un)controlled hypertension, and the effect of menopause on WMH. Therefore, our aim was to investigate these sex differences and age dependencies in WMH load across the adult life span and to examine the effect of menopause.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 50 publications
3
31
0
Order By: Relevance
“…Based on recent studies suggesting that tissue-specific age prediction can provide further detail ( Beck et al, 2022 , de Lange et al, 2020a , Eavani et al, 2018 , Voldsbekk et al, 2021 ), we estimated GM and WM brain age separately. WMH volume derived from T2 fluid-attenuated inversion recovery (FLAIR) images was examined as an additional measure, as a number of studies indicate higher WMH prevalence in females compared to males ( Alqarni et al, 2021 , Jorgensen et al, 2018 , Lohner et al, 2022 , Sachdev et al, 2009 , Than et al, 2021 , Van Den Heuvel et al, 2004 ) and recent evidence points to sex-specific associations between cardiometabolic risk factors and WMH pathology ( Alqarni et al, 2021 ). Sex differences in WMH prevalence have been observed to primarily emerge after the age of 50 ( Wen et al, 2009 ), which is close to the average age of menopause (51 years, ( InterLACE, 2019 )), or specifically after the menopause ( Jorgensen et al, 2018 , Lohner et al, 2022 , Than et al, 2021 ), indicating a link between WMHs and female endocrine ageing processes ( Thurston et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on recent studies suggesting that tissue-specific age prediction can provide further detail ( Beck et al, 2022 , de Lange et al, 2020a , Eavani et al, 2018 , Voldsbekk et al, 2021 ), we estimated GM and WM brain age separately. WMH volume derived from T2 fluid-attenuated inversion recovery (FLAIR) images was examined as an additional measure, as a number of studies indicate higher WMH prevalence in females compared to males ( Alqarni et al, 2021 , Jorgensen et al, 2018 , Lohner et al, 2022 , Sachdev et al, 2009 , Than et al, 2021 , Van Den Heuvel et al, 2004 ) and recent evidence points to sex-specific associations between cardiometabolic risk factors and WMH pathology ( Alqarni et al, 2021 ). Sex differences in WMH prevalence have been observed to primarily emerge after the age of 50 ( Wen et al, 2009 ), which is close to the average age of menopause (51 years, ( InterLACE, 2019 )), or specifically after the menopause ( Jorgensen et al, 2018 , Lohner et al, 2022 , Than et al, 2021 ), indicating a link between WMHs and female endocrine ageing processes ( Thurston et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…WMH volume derived from T2 fluid-attenuated inversion recovery (FLAIR) images was examined as an additional measure, as a number of studies indicate higher WMH prevalence in females compared to males ( Alqarni et al, 2021 , Jorgensen et al, 2018 , Lohner et al, 2022 , Sachdev et al, 2009 , Than et al, 2021 , Van Den Heuvel et al, 2004 ) and recent evidence points to sex-specific associations between cardiometabolic risk factors and WMH pathology ( Alqarni et al, 2021 ). Sex differences in WMH prevalence have been observed to primarily emerge after the age of 50 ( Wen et al, 2009 ), which is close to the average age of menopause (51 years, ( InterLACE, 2019 )), or specifically after the menopause ( Jorgensen et al, 2018 , Lohner et al, 2022 , Than et al, 2021 ), indicating a link between WMHs and female endocrine ageing processes ( Thurston et al, 2016 ). We used Bayesian linear models to assess relationships between the brain measures and VAT and ASAT, and included interaction terms to test if associations varied depending on reproductive span.…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that estrogens can increase tissue perfusion of the retina and brain probably by reducing vascular resistance, protecting against oxidative stress, and stimulating synaptogenesis in premenopausal women ( 34 , 35 ). However, estrogen levels decline markedly after the menopause, the vascular protection of estrogen disappears and women become more susceptible to vascular changes and diseases in the brain ( 34 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the MCI, V-MCI, and PD-CIE groups, women had significantly lower WMH volumes for bilateral occipital lobes. Sex specific differences in prevalence of WMHs might also be in part due to differences in prevalence of and susceptibility to underlying associated risk factors such as hypertension, diabetes and obesity, hypercholesterolemia, alcohol abuse, and smoking ( Bonberg et al, 2022 , Lohner et al, 2022 ). While we did not have this data available, investigating the prevalence of vascular risk factors in 51,338 Canadians, the Canadian Longitudinal Study of Aging (CLSA) have reported higher prevalence of hypertension, heart disease, diabetes, and midlife obesity in men, whereas women had higher rates of late life obesity ( Griffith et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%